Comparison of perioperative glucose regulation in patients with type 1 vs type 2 diabetes mellitus: A retrospective cross‐sectional study. Issue 3 (25th October 2018) - Hulst, Abraham H.; Polderman, Jorinde A. W.; Kooij, Fabian O.; Vittali, Dave; Lirk, Philipp; Hollmann, Markus W.; DeVries, J. Hans; Preckel, Benedikt; Hermanides, Jeroen
Abstract : Background: Most perioperative diabetes mellitus (DM) guidelines do not distinguish between patients with type 1 (DM1) and type 2 (DM2). We hypothesised that similar treatment of DM1 and DM2 patients leads to differences in their perioperative glucose control. Methods: We performed a retrospective cross‐sectional study, of all DM patients undergoing surgery between May 2013 and November 2015 in a Dutch university hospital. We compared DM1 with DM2 patients, treated according to the same perioperative glucose protocol. Our primary outcome was the incidence of hyperglycaemia (glucose ≥10 mmol/L). Secondary outcomes were short‐term glycaemic control (glucose before surgery and peak glucose perioperatively), long‐term glycaemic control (HbA1c in 90 days before and after surgery) and the incidence of hypoglycaemia (glucose <4 mmol/L). Results: We included 2259 patients with DM, 216 (10%) of which had DM1. The calculated incidences in our population were 7 out of 1000 patients with DM1 and 69 out of 1000 patients with DM2. Compared to those with DM2, patients with DM1 were younger, had a lower BMI, a higher glucose concentration before surgery, and a higher perioperative peak glucose concentration (11.0 [8.2‐14.7] vs 9.4 [7.7‐11.7], P  < 0.001). The incidence of the primary endpoint, perioperative hyperglycaemia, was significantly higher in DM1 compared to DM2 patients (63% vs 43%, P  < 0.001). Hypoglycaemia occurred more often in the DM1 population (7.1% vs 1.3%, P  < 0.001). Conclusion: Providing similar perioperative treatment to patients with DM1 and DM2 is associated with poorer short‐term and long‐term glycaemic control in DM1 throughout the perioperative period as well as an increased risk of hypoglycaemia.